Spectrally blue hydrated parent body of asteroid (162173) Ryugu - Eri Tatsumi (Nature Portfolio, 2021)
Both poles of asteroid Ryugu, the target of space mission Hayabusa2, preserve the least processed material by space weathering. Here, the authors show detection of 700 nm absorption band in the polar spectra of Ryugu, that allows to constrain the hydrothermal history of its spectrally blue parent body.